2021
DOI: 10.1891/lgbtq-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders Mediates the Association between Sexual Orientation Discrimination and Substance Use Disorders among Sexual Minority Adults

Abstract: Although sexual orientation discrimination (SO-discrimination) is associated with an increased risk of psychiatric and substance use disorders (SUD) among sexual minority (SM) adults, these relationships are not well understood, particularly in the context of SUD severity. To address this gap, we assessed the direct and indirect effect of SO-discrimination and sexual identity on psychiatric disorders and SUD severity in the context of stress and resilience among SM adults. We used data from 3,494 adults report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, in a U.S. probability sample of sexual minorities, 72 to 81% had been verbally insulted or abused, 46 to 61% had been threatened with violence, and 37 to 51% had been hit, beaten, physically attacked, or sexually assaulted (Meyer et al, 2021). In line with the minority stress model, research has consistently demonstrated that sexual orientation-related discrimination is a robust risk factor for adverse mental and physical health outcomes (e.g., depression, anxiety, non-suicidal self-injury, substance use disorders, poor physical health, HIV infection; Flentje et al, 2020; Jeffries et al, 2021; Kahle et al, 2021; Lee et al, 2016; Liu et al, 2019; Meyer & Frost, 2013). Based on these findings, discrimination represents a major public health concern with significant consequences for the health of sexual minorities.…”
mentioning
confidence: 91%
“…Furthermore, in a U.S. probability sample of sexual minorities, 72 to 81% had been verbally insulted or abused, 46 to 61% had been threatened with violence, and 37 to 51% had been hit, beaten, physically attacked, or sexually assaulted (Meyer et al, 2021). In line with the minority stress model, research has consistently demonstrated that sexual orientation-related discrimination is a robust risk factor for adverse mental and physical health outcomes (e.g., depression, anxiety, non-suicidal self-injury, substance use disorders, poor physical health, HIV infection; Flentje et al, 2020; Jeffries et al, 2021; Kahle et al, 2021; Lee et al, 2016; Liu et al, 2019; Meyer & Frost, 2013). Based on these findings, discrimination represents a major public health concern with significant consequences for the health of sexual minorities.…”
mentioning
confidence: 91%